Treatment of Supraorbital Neuralgia Using Ultrasound-Guided Radiofrequency Thermocoagulation of the Supraorbital Nerve: A Retrospective Study - Ren H; Shen Y; Luo F (Journal of Pain Research, 2020)
Hao Ren, Ying Shen,* Fang Luo* Department of Pain Management, Beijing Tiantan Hospital, Capital Medical University, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fang Luo; Ying ShenDepartment of Pain Management, Beijing Tiantan Hospital, Capital Medical University, No. 119 West Road, South 4th Ring Road, Fengtai District, Beijing 100050, People’s Republic of ChinaTel +86 13611326978; +86 18610791617Email luofangwt@yahoo.com; shenying1937@hotmail.comPurpose: There is no standard clinical treatment protocol for supraorbital neuralgia patients who respond poorly to conservative treatment. Radiofrequency thermocoagulation, a neurologically damaging procedure, is a treatment for supraorbital neuralgia. However, assessments of its long-term efficacy are lacking. Thus, this study aimed to evaluate the long-term efficacy and safety of ultrasound-guided radiofrequency thermocoagulation for treating supraorbital neuralgia.Patients and Methods: We retrospectively reviewed our clinical database for supraorbital neuralgia patients who underwent an ultrasound-guided radiofrequency thermocoagulation procedure. Demographic data and baseline characteristics, time of onset, postoperative pain intensity, time of recurrence, subsequent treatment, complications and side effects were collected and analysed. The Kaplan-Meier estimator was used to determine recurrence-free survival.Results: A total of 53 supraorbital neuralgia patients were included in this study. All patients experienced complete pain relief within one month. The median follow-up time of the 53 patients was 36.0 months (IQR, 12.0– 72.0 months). A total of 13 patients experienced pain recurrence, with a median recurrence-free time of 97 months according to the Kaplan-Meier estimator. The cumulative proportion of recurrence-free survival was 96.2% at 12 months, 88.4% at 24 months, 82.7% at 36 months, 70.0% at 48 months, 66.3% at 60 months, and 49.7% at 97 months. All but one patient with recurrent pain underwent a second or third radiofrequency thermocoagulation procedure and achieved complete pain relief. Numbness of supraorbital nerve innervation occurred in all patients. However, the numbness scores gradually decreased over time.Conclusion: Ultrasound-guided radiofrequency thermocoagulation is a safe, effective treatment for supraorbital neuralgia patients who respond poorly to conservative treatments. These patients attained excellent long-term pain relief with a gradual reduction in numbness.Keywords: supraorbital neuralgia, radiofrequency thermocoagulation, long-term efficacy, survival analysis